Effective Communication Strategies for Nurses to Discuss Infant Feeding with New Mothers During Postpartum Hospitalization. Issue 4 (July 2018) - Wood, Rainey Banick
Abstract : Abstract: During prenatal care and postpartum hospitalization, nurses have an important role in assisting new mothers to make informed decisions about feeding their newborn infants. There is overwhelming evidence that breastfeeding is beneficial for most new mothers and babies; therefore, perinatal nurses encourage breastfeeding. Newborn infant feeding conversations with women who have chosen to formula feed may be complicated and may cause tension in the nurse–patient relationship. Despite this potential difficulty, these conversations are essential to establish a feeding plan for the newborn infant and to promote healthy outcomes for mothers and babies. Tools are offered for nurses to guide conversations about infant feeding choices and to help to ensure that all mothers receive support and encouragement on their feeding choice. Abstract : Nurses offer education and support to new mothers on infant feeding during postpartum hospitalization. There is overwhelming evidence that breastfeeding is best for most mothers and babies, however not all mothers choose to breastfeed and breastfeeding is contraindicated in some cases. Effective communication techniques to discuss infant feeding options are offered, with an emphasis on providing a supportive, therapeutic discussion with new mothers who choose to formula feed their babies.